THE MEDIC-STATISTICAL CHARACTERISTIC INCIDENCE OF PNEUMONIA IN THE UDMURT REPUBLIC - E. S. Bobyleva; A. Yu. Gorbunov; O. I. Starodubtsevа; Ya. M. Vakhrushev (Архивъ внутренней медицины)
The Community-acquired Pneumonia (CAP) is an urgent problem of modern medicine owing to its high prevalence, gravity of a current, the increasing resistance of a microflora to antibacterial therapy, a large number of complications and a high lethality. Udmurt republic is one of leaders among the regions of Russian Federation on morbidity by diseases of the respiratory system, include CAP. It is therefore necessary to take analysis and prognosis incidence for the future improving quality administer. Research objective. The analysis of incidence and mortality from diseases of respiratory organs in the Udmurt Republic for 2009-2016. Materials and methods. The retrospective and prospection clinical-epidemiological research of prevalence and primary incidence of diseases of respiratory organs among the adult population of the Udmurt Republic living in 4 cities is conducted (Izhevsk, Sarapul, Glazov, Votkinsk) and 25 rural areas for the 8-summer period (2009-2016). The analysis is carried out on the basis of data of the state statistical registration and reporting documentation of Budgetary institution of health care of the Udmurt Republic «Republican medical information and analysis center of the Ministry of Health of the Udmurt Republic». Results of a research. The prevalence of diseases of respiratory organs in the Udmurt Republic was 49871,39±1,33 on 100 thousand population. The average growth rate was 2,3%, and the average rate o f a gain was — 0,25%. In comparison with data for the same period to the Russian Federation, average growth rate the average rate of a gain — 5,48% was 1,7%, and that demonstrates some decrease in incidence. In the analysis of structure of incidence of diseases of respiratory organs of the population of the Udmurt Republic it is established that she throughout the entire period of observation significantly hasn’t changed. At the same time annually, leading places are taken by pneumonia and the chronic obstructive pulmonary disease (COPD). Estimating the level of primary incidence of diseases of respiratory organs, it is noted that on UR the average growth rate is 105,42%, the average rate of a gain of 5,42%, in comparison across the Russian Federation average growth rate of 87,07%, and the average rate of a gain — 12,93%. Conclusion. Thus, to UR, as well as in general across the Russian Federation steadily high incidence of pneumonia is noted. At the same time the tendency to increase in incidence and this pathology mortality is noted. This circumstance demands further studying of a problem of pneumonia, including improvement of methods of medical correction.